2015
DOI: 10.1002/rcm.7227
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of fenbuconazole under UV‐visible irradiation – chemical and toxicological approaches

Abstract: UV-visible irradiation of fenbuconazole in aqueous solution and on grapes leads to the formation of isomers, all of which being potentially much more toxic than the parent fungicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Statistically significant degradation was faster on apple skin (15 min, 4815 mJ/cm 2 ) than on glass (30 min, 9342 mJ/cm 2 ) (Tables 3 & 4). Lassalle et al (2015) had previously shown cyclization of fenbuconazole as a result of irradiation with UV light of an aqueous solution in 120 mL quartz tubes in a sonicator using a high-pressure mercury lamp producing light between 200 nm and 650 nm. The degradation of fenbuconazole was not quantified by Lassalle et al (2015) though formation and identification of eight isomers of fenbuconazole suggests there was a reduction in the amount of fenbuconazole in the solution.…”
Section: Fenbuconazolementioning
confidence: 99%
“…Statistically significant degradation was faster on apple skin (15 min, 4815 mJ/cm 2 ) than on glass (30 min, 9342 mJ/cm 2 ) (Tables 3 & 4). Lassalle et al (2015) had previously shown cyclization of fenbuconazole as a result of irradiation with UV light of an aqueous solution in 120 mL quartz tubes in a sonicator using a high-pressure mercury lamp producing light between 200 nm and 650 nm. The degradation of fenbuconazole was not quantified by Lassalle et al (2015) though formation and identification of eight isomers of fenbuconazole suggests there was a reduction in the amount of fenbuconazole in the solution.…”
Section: Fenbuconazolementioning
confidence: 99%
“…Six compounds (TP3–TP8) yield a [M + H] + ion at m/z 226 and have the same elemental composition as cyprodinil. Isomerization reactions have been obtained previously by irradiation of fungicides . The corresponding compounds in the irradiated cypro‐D 5 solution are all shifted by +5 mass units.…”
Section: Resultsmentioning
confidence: 99%
“…[16] TP1 loses either NH 3 from the form protonated on the amino function to give m/z Table 5. Proposed structures and associated in silico predicted toxicity values for oral rat LD50 for cyprodinil and its isomers TP1, TP2 and TP14 [25,26] The corresponding compounds in the irradiated cypro-D 5 solution are all shifted by +5 mass units. Moreover, the six CID mass spectra look very similar and provide the same product ions as those observed for cyprodinil, although with different relative intensities.…”
Section: Chemical Analysis Of Cyprodinil Photoproductsmentioning
confidence: 99%